Keanekaragaman dan Kelimpahan Musuh Alami Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) pada Pertanaman Cabai Merah di Kecamatan Pakem, Kabupaten Sleman, Daerah Istimewa Yogyakarta - Hendrival Hendrival; Purnama Hidayat; Ali Nurmansyah (Jurnal Entomologi Indonesia, 2011)
Research on natural enemies of Bemisia tabaci was conducted in the chili pepper fields in Sub-district of Pakem, District of Sleman, The Special Province of Yogyakarta during the dry season of May-October 2009. The aims of this research were to study the diversity and abundance of parasitoid and predator species associated with B. tabaci. Samplings of insect species were done using yellow pan trap, sweep net, direct observation of insects colonized young leaves, and collection of nymphs for B. tabaci. Measurement of insect diversity was calculated using Shannon’s index diversity and Evenness index. Nine species of insect predator were identified, i.e. Harmonia octomaculata (Fabricius), Menochilus sexmaculata (Fabricius), Scymnus sp., Micraspis inops Mulsant, Coccinella sp. (Coleoptera: Coccinellidae), Paederus fuscipes Curtis (Coleoptera: Staphylinidae), Orius sp. (Hemiptera: Anthocoridae), Linyphiidae sp.1 (Araneae), and Syrphidae sp.1 (Diptera). Eretmocerus sp. (Hymenoptera: Aphelinidae) was the only parasitoid found in the nymphs B. tabaci collected and has the potential to control B. tabaci in the red pepper fields.